The Voyage of the dawn treader - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline; HarperCollins Children's Books (London : HarperCollins Children's Books, 2001)
Lucy and Edmund, accompanied by their peevish cousin Eustace, sail to the land of Narnia where Eustace is temporarily transformed into a green dragon because of his selfish behavior and skepticism.
Keywords: Narnia (Imaginary place) -- Fiction; Fantastic fiction